Evaluating Saudi cement companies' market share. Issue 2 (3rd July 2017) - Alsultanny, Yas; AlZuhair, Sara
Abstract : Purpose: The purpose of this paper is to evaluate the Saudi cement companies' market share. Design/methodology/approach: The data collected from the annual reports and financial statements of 12 companies. Findings: The analysis of the production indicators showed that seven Saudi companies had a steady state of production capacity, while the other five companies had an increase in their production capacity. Research limitations/implications: The research is limited to the Saudi cement companies. Practical implications: The Saudi cement companies add expenditures annually to update their managerial technologies, production equipment and machinery in plants and processes. Originality/value: The Saudi cement companies must be creating more competition between the cement companies through the opportunity of developing or acquiring new technologies.